SCIENTIFIC-THEORETICAL APPROACHES TO FORMING READING CULTURE IN PRIMARY EDUCATION (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
Reading culture - the sustained habit of reading coupled with the capacity for critical comprehension, aesthetic appreciation, and independent interpretive engagement - represents one of the most significant yet underexplored dimensions of primary education. While considerable scholarly attention has been directed toward reading literacy as a measurable outcome, the formation of reading culture as a dispositional orientation toward text has received comparatively less systematic theoretical treatment. This article synthesises key scientific-theoretical approaches to the cultivation of reading culture in primary school learners, drawing upon motivational, cognitive, socio-cultural, and reader-response frameworks. The study examines how phonics-based, whole-language, and balanced-literacy traditions conceptualise the emergence of genuine reading engagement beyond mere decoding proficiency